ANALISIS VARIABEL – VARIABEL YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN KONSUMEN KOPI LUWAK DI KOTA SEMARANG - Novel, Belgis; Tri Astuti, Sri Rahayu (Faculty of Economics and Business Diponegoro University, 2015)
The purpose of this research are to check the effect of the product quality, price competitiveness, and distribution effect on consumer's decision to buy Kopi Luwak in Semarang. TheÂ deflation of Kopi Luwak's selling rate in Semarang is taken as the background of this research. This research is using the questionaire methode to collect the data from 100 sample respondent, the sampling technic used is convenience sampling and data analysis used in this research is multiple linear regression method. The result of this research shows that all the independent variables which are product quality, price competitiveness, and distribution have a positive relation and significant to the dependant variable in which is consumer's decision to buy the product. On the independent variable, distribution variable took the major influence to the dependant variable to consumer's decision to buy the product, this is shown on the coefficient point at 0,520. The result is because of respondents are always find it easy to get Kopi Luwak's product and the product is always available in the market.